2013
DOI: 10.1053/j.gastro.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Molecular Analysis of Intrahepatic Cholangiocarcinoma Reveals 2 Classes That Have Different Outcomes

Abstract: BACKGROUND & AIMS Cholangiocarcinoma, the second most common liver cancer, can be classified as intra-hepatic cholangiocarcinoma (ICC) or extrahepatic cholangiocarcinoma. We performed an integrative genomic analysis of ICC samples from a large series of patients. METHODS We performed a gene expression profile, high-density single-nucleotide polymorphism array, and mutation analyses using formalin-fixed ICC samples from 149 patients. Associations with clinicopathologic traits and patient outcomes were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
499
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 481 publications
(524 citation statements)
references
References 52 publications
16
499
2
7
Order By: Relevance
“…Our findings are in line with recently published smaller series detecting BRAF mutations in 1% to 4% of evaluated cases. [26][27][28] We cannot confirm the exceedingly high mutation rates detected in early BRAF studies of European cohorts, 29,30 and conclude that the previously assumed regional difference in the genetics of biliary tract cancer in Europe versus the Americas is not existent. 2 Our data further demonstrate that BRAF mutations are restricted to intrahepatic cholangiocarcinomas and account for 3% in this subgroup.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our findings are in line with recently published smaller series detecting BRAF mutations in 1% to 4% of evaluated cases. [26][27][28] We cannot confirm the exceedingly high mutation rates detected in early BRAF studies of European cohorts, 29,30 and conclude that the previously assumed regional difference in the genetics of biliary tract cancer in Europe versus the Americas is not existent. 2 Our data further demonstrate that BRAF mutations are restricted to intrahepatic cholangiocarcinomas and account for 3% in this subgroup.…”
Section: Discussionmentioning
confidence: 62%
“…In two previously analyzed cholangiocarcinoma cohorts, tumors with BRAF mutations other than V600E have been reported that may potentially also respond to targeted therapy. For BRAF V600K (detected in one intrahepatic cholangiocarcinoma by Sia et al 27 ) response of melanoma metastases has been observed in a phase II trial, 37 and for BRAF V600D (detected in two cholangiocarcinomas not otherwise specified by Tannapfel et al 29 ) in vitro inhibitor Figure 2 Overall survival probability in intrahepatic cholangiocarcinoma patients in correlation with BRAF V600E status. Kaplan-Meier curves show no difference in overall survival of patients in correlation with BRAF V600E status in intrahepatic cholangiocarcinoma (P ¼ 0.38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide an overview of the genomic landscape of molecular alterations in iCCA, we integrated exome-and RNA-seq data with our previously published iCCA molecular classification 5 . IDH1 and IDH2 mutations were observed in 11 (11/107, 10%) and 7 patients, respectively (7/107, 7%, Supplementary Table 10).…”
Section: T C a C A A C C A A T G A G -G A T G G C T A C A A T A G T Cmentioning
confidence: 99%
“…Of late, there has been a significant improvement in our understanding of the molecular basis of iCCA 4 . Large-scale molecular profiling studies have enabled the first molecular classifications to emerge 5,6 . Furthermore, deepsequencing studies have provided a preliminary description of somatic mutations for iCCA [7][8][9][10] : novel mutations in chromatin remodelling genes (BAP1, ARID1A and PBRM1) have been recently unveiled, whereas frequent mutations in KRAS, IDH1 and IDH2 have been confirmed [8][9][10][11] .…”
mentioning
confidence: 99%